2021
DOI: 10.1021/acs.iecr.1c03393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on the Effect of Magnetic Field on the Crystallization of Organic Small Molecules

Abstract: Exploring the effect of magnetic field on crystallization process and revealing the mechanism of magnetic field can enrich the regulation and intensification methods of crystallization process. In this paper, the effect of magnetic field on crystal nucleation and growth and its mechanism were comprehensively studied from the perspective of crystallization thermodynamics and kinetics, using a small organic molecule polyamide 56 salt as the model compound. The solubility, nucleation kinetics, and growth kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Thermodynamic parameters of the dissolution process were fitted and calculated by the van’t Hoff equation as expressed in eq . , ln nobreak0em.25em⁡ x 1 = prefix− normalΔ H normald italicRT + normalΔ normalS normald R where Δ H d and Δ S d are the dissolution enthalpy and entropy, respectively. , Using the natural logarithm of the solubility of cytidine sulfate (ln x 1 ) versus 1/ T plot, as shown in Figure , Δ H d and Δ S d were obtained from the slope and the intercept, respectively . Besides, in order to calculate the Gibbs free energy (Δ G d ), the relative contributions of enthalpy (%ξ H ) and entropy (%ξ TS ) in the dissolution process, eq , , and were employed. , normalΔ G normald = normalΔ H normald T normalm · normalΔ S normald % ξ normalH = false| normalΔ H normald false| | Δ H d | + | T m Δ S d | × 100 …”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic parameters of the dissolution process were fitted and calculated by the van’t Hoff equation as expressed in eq . , ln nobreak0em.25em⁡ x 1 = prefix− normalΔ H normald italicRT + normalΔ normalS normald R where Δ H d and Δ S d are the dissolution enthalpy and entropy, respectively. , Using the natural logarithm of the solubility of cytidine sulfate (ln x 1 ) versus 1/ T plot, as shown in Figure , Δ H d and Δ S d were obtained from the slope and the intercept, respectively . Besides, in order to calculate the Gibbs free energy (Δ G d ), the relative contributions of enthalpy (%ξ H ) and entropy (%ξ TS ) in the dissolution process, eq , , and were employed. , normalΔ G normald = normalΔ H normald T normalm · normalΔ S normald % ξ normalH = false| normalΔ H normald false| | Δ H d | + | T m Δ S d | × 100 …”
Section: Resultsmentioning
confidence: 99%
“…6 Specifically, the structure or the physicochemical property of the composition in the gel may have been changed due to the MF, which in turn led to the increased activity of the immobilized enzyme. 33 The specific reasons were explored in the next part of the experiment. Besides, the effect of MF–enzyme was worse than MF–sol, which may be attributed to that the structure of the enzyme solution having been changed by the gel network after magnetization or that the magnetization structure gradually disappears during a long drying process.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic fields inhibit the growth of protein crystal faces, but the mechanism of magnetic fields on different crystal faces of proteins is still unclear. Recently, the effect of a magnetic field on the crystallization process of organic small molecules has also been investigated . The results showed that the magnetic field increased the solubility of polyamide salts in water due to the competition between the magnetic field-induced reverse motion of the particles and the inherent random Brownian motion of the particles in the crystalline system, which led to the prolongation of the nucleation induction time, the widening of the metastable zone, and the increase of the nucleation potential barrier.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 99%